Economic assessment of coral reef ecosystems in Bajo Gurapin waters, Kayoa district, South Halmahera - Alhaddad, M. Said; Kader, Iwan Hi.; Abdulkadir, Maskur (Agrikan: Jurnal Agribisnis Perikanan, 2021)
Coral reefs are one of the most productive and most diverse coastal ecosystem. This ecosystem is the habitat of marine biota such as reef fish, molluscs, crustacea, seaweed, marine plants and so on that use this place as a place to breed, look for food and protection (Romimohtarto, 1991). Coral reef ecosystems are one of the natural resources, where coastal communities benefit from these resources. This study aims to determine the shape of coral reefs (lifeform) and the percentage of coral reefs, and to estimate the economic benefits of coral reef ecosystems in the waters of Bajo-Guruapin Village, Kayoa District, South Halmahera Regency, North Maluku Province. in the waters of Bajo - Guruapin are Acropora Branching (ACB), Acropora Submassive (ACS), Acropora Tabulate (ACT), Coral Branching (CB), Coral Encrusthing (CE), Coral Massive (CM), Coral Foliose (CF), Coral Submassive (CS) and Soft Coral (SC). From the results of the analysis, the percentage of coral cover ranged from 35.65 to 74.42% consisting of hard corals and soft corals so that the condition of coral reefs in Bajo - Guruapin waters can be categorized as conditions up to good.